Supporting women to achieve breastfeeding to six months postpartum – The theoretical foundations of a successful program. Issue 4 (December 2015) - Meedya, Shahla; Fahy, Kathleen; Parratt, Jenny; Yoxall, Jacqui
Abstract: Background: Although the benefits of breastfeeding to six months are well-established, only about half of Australian women succeed. The factors associated with successful breastfeeding are rarely translated into effective interventions. A new educational and support program, called the Milky Way program has been demonstrated to be effective in supporting women to achieve prolonged breastfeeding. In the Milky Way program, breastfeeding is considered an embodied performance which requires an engaged combination of body, mind and spirit. This paper aims to explain how the two theories that informed the program were used to better enable women's long term breastfeeding success. Method: The theory of self-efficacy is first described as a way to develop women's cognitive processes to organise and execute the course of actions to breastfeed for a longer period of time. Birth territory theory is then presented. This theory discusses women as embodied selves; an essential concept for breastfeeding success. Birth territory theory also describes the effects of the holistic environment on the woman and explores the effects of power that is used in the environment. This power can be used integratively to strengthen the woman's breastfeeding confidence and success or, disintergratively which reduces her confidence and undermines her success. Conclusion: Strategies based on self-efficacy theory are helpful, but are not sufficient to promote breastfeeding to six months. Health educators also need to foster the woman's connection to, and trust in, her body and her baby's body to breastfeed spontaneously. Being aware of environmental impacts on how the woman and baby breastfeed; and using one's own power integratively is crucial to women being able to achieve prolonged breastfeeding.